Pelaksanaan Program Pemberian Makanan Tambahan Pemulihan pada Balita Gizi Kurang di Kabupaten Kampar - Amalia, Rica; Harahap, Heryudarini; Nurlisis (IPTEKIN Jurnal Kebijakan Pembangunan dan Inovasi, 2018)
Malnutrition is still a problem in community and it is cause of mortality in high risk groups of infant and toodlers. One of way to solve malnutrion problems in Kampar district is supplementary feeding program recovery (PMT-P) from ministry of health. PMT-P is biscuits for 90 days. This study was to evaluate the implementation of PMT-P program in district of Kampar. The study was observational and used qualitative research. The study informants consisted of three main informants and 16 second informant. The study was conducted in 3 primary healthcare centers and undernourished children as a subject.The data was conducted by in-depth interviews. The PMT-P program in the Kampar District was not carried out according to the standards and stages of the Ministry of Health technical guidelines. The preparation stage was not maximal, such as socialization/ counseling, and formation of the target group was not created. The stage of implementation was the distribution and counseling was not gone well. The monitoring stage such as home visited, length measurements was not conducted in all children. The recording was not done properly by the midwife. No record of the number of biscuits consumed by mothers and village midwives. Reporting was not yet an obligation to do. It is recommended for all stakeholders to implement the PMT-P program in accordance with the existing provisions.